A study of optimal design process for complex-shaped skyscrapers’ structural systems in United Arab Emirates - Chuloh Jung; Riyad Awad; Jihad Awad (Ain Shams Engineering Journal, 2022)
Contemporary atypical skyscrapers in United Arab Emirates became the landmarks of the city and secured the urban competitiveness via innovative building design. These contemporary skyscrapers use non-linear geometry of structural frames, it is impossible to design these structures with conventional design methods. The objective of this paper is to examine the unit technologies for structural design of an atypical skyscraper and propose an optimal structural design process. As a methodology, the status of atypical skyscraper optimization technologies is analyzed, the status of data exchange among structural analysis programs, BIM software and FEM analysis programs are examined, and the case studies of some landmark buildings in United Arab Emirates designed by well known companies such as SOM, AECOM, and Salama Structural Engineers are explored. The result has shown that the unit technologies for optimizing atypical skyscrapers can follow four phases: Concept Design Phase, Schematic Design Phase, Design Development Phase and Construction Documentation Phase.